Managing innovation of care services: An exploration of Norwegian municipalities - Tor Helge Aas; Nina Jentoft; Mikaela Vasstrøm (Cogent Business & Management, 2016)
The social impact of care services provided by the public sector is significant. Nevertheless, these services have received relatively little attention from prior innovation management practices research. This paper addresses this gap by raising the question: What characterises management-driven innovation processes in public organisations providing care services? The qualitative exploration of this question is based on in-depth interviews with key managers in three Norwegian municipalities, and in-depth observation of one ongoing innovation initiative in one municipality. Our findings supplement the findings of prior research by showing that different actors are involved in different stages of management-driven innovation processes in care services and by showing that employee-based “bricolage” may be an integrated part of management-driven innovation processes in this sector. The findings provide both managerial implications and implications for further research.
Keywords: 650